Pengaruh Beban Kerja Terhadap Kinerja Guru Sekolah Menengah Kejuruan Keuangan Pekanbaru - Nurhayana Nurhayana (Eko dan Bisnis: Riau Economic and Business Review, 2025)
This research was conducted at the Vocational School of Finance in Pekanbaru, located on Jl. Gulama, Pekanbaru. The purpose of this study was to determine the effect of workload on teacher performance at the Vocational School of Finance in Pekanbaru. Data analysis in this study used a quantitative method, namely research based on quantifiable data to produce robust estimates. The sample size was 86 people. The results of a simple linear regression were obtained: Y = 15.631 + 639 X. Using the t-test, the t-table value was 1.988 and the calculated t-value was 15.631. This means that t-count = 15.531 > t-table = 1.988, indicating that workload affects teacher performance at the Vocational School of Finance in Pekanbaru. The adjusted R-squared result of 0.530 indicates that workload influences teacher performance at Pekanbaru Financial Vocational School by 53%, with the remaining 47% influenced by other variables not examined in this study.